Obesity and cholangiocarcinoma: A review of epidemiological and molecular associations. (17th June 2021) - Osataphan, Soravis; Mahankasuwan, Treerat; Saengboonmee, Charupong
Abstract: Cholangiocarcinoma (CCA) is a malignancy of bile duct epithelium, and its incidence is increasing globally. Numerous factors are reported associated with an increased risk of CCA and vary among populations across different areas. Obesity is a major, worldwide public health problem that leads to several complications and is associated with increased cancer risk. Although several epidemiological studies have shown that obesity is likely associated with the increased risk of CCA, this association might be limited to Western countries. Multiple hormones, cytokines, and metabolite perturbations in obese states have been shown to enhance tumorigenicity and metastasis potentials. Understanding the biological linkage of obesity to CCA might lead to novel prevention and therapeutic approaches to CCA treatment. This review summarizes the current evidence and highlights the knowledge gaps regarding the relationship between obesity and CCA from epidemiological and molecular perspectives. Abstract : Highlight Osataphan and colleagues reviewed studies on the associations between obesity and cholangiocarcinoma and found that an increased risk of cholangiocarcinoma in people with obesity is mostly reported in Western countries whereas most studies in Asia report a null effect. The possible biological linkages between obesity and cholangiocarcinoma are also discussed.